Oprah : a biography - Kelley, Kitty. frey50 (New York : Crown Publishers, 2010)
Based on three years of research and reporting as well as 850 interviews with sources, many of whom have never before spoken for publication, Oprah is the first comprehensive biography of one of the most influential, powerful, and admired public figures of our time. Anyone who is a fan of Oprah Winfrey or who has followed her extraordinary life and career will be fascinated and newly informed by the closely observed, detailed, and well-rounded portrait of her provided by Kitty Kelley's exhaustively researched book. Readers will come away with a greater appreciation of who Oprah really is beyond her public persona and a fuller understanding of her important place in American cultural history.--From publisher description.
Keywords: Winfrey, Oprah; Winfrey, Oprah; Television personalities -- United States; Actors -- United States; Television personalities -- United States; Actors -- United States